Students' metaphoric perceptions regarding online education process including English language, English instructors and future life - Kubra Aksak; Feryal Cubukcu (Literacy Trek, 2023)
The aim of the present study is to investigate the perceptions of prep-class students regarding online education along with English instructors, English language and their future life. Hermeneutic phenomenology method was employed and metaphors were used as a data collection tool to gather information from 80 prep-class students selected through convenience sampling method. The findings indicated that more than half of the participants (52.5%) have a negative attitude towards online education. A considerable number of students (73.7%) have a quite positive perception of English instructors. "Universal language, new world, new people" are among the most preferred metaphors for the participants' perceptions of English language. Moreover, 66.3% of the students are pessimistic about their future life. Hence, students are not in favor of online education although it is flexible and comfortable, which implies that online education should be a secondary option only when face-to-face education is impossible to implement.